2015
DOI: 10.1017/s0031182014001188
|View full text |Cite|
|
Sign up to set email alerts
|

Parasites in fisheries and mariculture

Abstract: Traditionally, parasitology has been concerned with the harmful effects of parasitic organisms; it is basically an applied science. Since its founding in the field of medicine, and later in veterinary medicine, parasitology has been mainly devoted to generating knowledge, which is applicable to parasite control and management, and eventually to their eradication. However, the complexity of parasitism, as revealed over recent decades by workers in various specialisms of parasitology, makes the application of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…For instance, the highveld region in Zimbabwe, characterised by wet/swampy grazing areas where distribution of snail habitats is widespread, is associated with a higher prevalence compared with the lowveld which is characterised by dry land grazing with a focal distribution of snail habitats (Pfukenyi et al 2005a , 2005b ). Similarly, the presence of wetlands and high livestock density in the cattle grazing areas of the Zambian western and southern provinces is associated with an increased risk of acquiring amphistome infections (Phiri et al 2006 ) and the same observations have been reported in Kenya (Kanyari et al 2009 , 2010), Tanzania (Keyyu et al 2005 , 2006; Nzalawahe et al 2015 ) and Uganda (Howell 2011 ). In Tanzania, traditional communal grazing areas exhibited the highest prevalence of amphistomes compared with other sectors and this is attributed to heavy contamination of the habitats with eggs where intermediate host snails breed, because of high stocking densities with subsequent heavy metacercarial density on vegetation grazed by the animals especially during the dry season (Keyyu et al 2005 , 2006).…”
Section: Epidemiological Features Of Amphistome Infections In Ruminanmentioning
confidence: 79%
See 1 more Smart Citation
“…For instance, the highveld region in Zimbabwe, characterised by wet/swampy grazing areas where distribution of snail habitats is widespread, is associated with a higher prevalence compared with the lowveld which is characterised by dry land grazing with a focal distribution of snail habitats (Pfukenyi et al 2005a , 2005b ). Similarly, the presence of wetlands and high livestock density in the cattle grazing areas of the Zambian western and southern provinces is associated with an increased risk of acquiring amphistome infections (Phiri et al 2006 ) and the same observations have been reported in Kenya (Kanyari et al 2009 , 2010), Tanzania (Keyyu et al 2005 , 2006; Nzalawahe et al 2015 ) and Uganda (Howell 2011 ). In Tanzania, traditional communal grazing areas exhibited the highest prevalence of amphistomes compared with other sectors and this is attributed to heavy contamination of the habitats with eggs where intermediate host snails breed, because of high stocking densities with subsequent heavy metacercarial density on vegetation grazed by the animals especially during the dry season (Keyyu et al 2005 , 2006).…”
Section: Epidemiological Features Of Amphistome Infections In Ruminanmentioning
confidence: 79%
“…Indigenous cattle breeds were observed to have a significantly higher prevalence and intensity than the exotic breeds and crosses in Kenya and Uganda (Howell 2011 ; Kanyari, Kagira & Mhoma 2010 ). In Tanzania, the Maasai Zebu cattle had a significantly higher prevalence than the Iringa Red cattle; however, the numbers of animals involved were too small for any meaningful interpretations to be made (Nzalawahe et al 2015 ). Literature reports a variable effect of sex in domestic ruminants.…”
Section: Epidemiological Features Of Amphistome Infections In Ruminanmentioning
confidence: 99%
“…Any inventory of parasite biodiversity and the proposition of well-supported hypotheses about their evolutionary histories depends on the sensitive detection and correct identification of species. The enormous realm of wildlife parasites remains largely underexplored and the occurrence of cryptic, clandestine and misclassified parasite species further complicates the prospect of such an inventory ( Criscione et al., 2005 , Bickford et al., 2007 , De León and Nadler, 2010 ; Detwiler et al., 2010 ; Nadler and De León, 2011 , Poulin et al., 2011b , Bray and Cribb, 2015 ). Further studies are required to assess whether the specificity of the crocodilian trypanosomes is restricted to closely related crocodilian species or whether they can exploit distantly related hosts of other taxa across their broad geographic range ( Poulin et al., 2011a ).…”
Section: Discussionmentioning
confidence: 99%
“…Along the Scandinavian peninsula, the Norwegian spring spawning herring stock (NSS) is currently distributed from off south-west Norway to the Barents Sea, and across the Norwegian Sea up to the eastern coast of Iceland (Subareas I and II, Fig. 1) (Levsen and Lunestad, 2010;Pampoulie et al, 2015;ICES, 2016c).Metazoan parasites are commonly used as biological tags for fish stock discrimination, allowing to gain information on the biology, individual origin, intraspecific population dynamics, as well as migration and life history of actual fish host species (Parmanne et al, 1994;MacKenzie, 2002;Klimpel et al, 2004;Hatfield et al, 2005;Cross et al, 2007;Levsen and Lunestad, 2010;Karl and Levsen, 2011;Mattiucci et al, 2014a;Münster et al, 2015;Timi and Mackenzie, 2015;Klapper et al, 2016). Among metazoan parasites, Anisakis spp.…”
Section: Introductionmentioning
confidence: 99%